2006
DOI: 10.1007/s10549-006-9388-4
|View full text |Cite
|
Sign up to set email alerts
|

A strong association between body fat mass and protein profiles in nipple aspirate fluid of healthy premenopausal non-lactating women

Abstract: Fluid can be aspirated from the nipples of most non-lactating women. This nipple aspirate fluid (NAF) is a potential source for the discovery of new breast cancer biomarkers. NAF has two distinct protein profiles. Type I NAF is similar to the fluid associated with cystic disease of the breast, whereas type II NAF is enriched in milk-associated proteins. The prevalence of these two profiles differs in healthy women and in breast cancer patients. This study investigated the relationship of these two NAF profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
2
3
0
Order By: Relevance
“…Thus, in women with large breasts, tissue estrogen levels would also be higher due to the larger amount of fat tissue. This idea agrees with a report that women with a nipple aspirate fluid (NAF) phenotype characterized by higher BMI and percentage body fat had higher NAF estrogen levels [ 41 ]. Therefore, the higher PR expression in women with large breasts as compared to women with small breasts may reflect responsiveness to estrogen [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, in women with large breasts, tissue estrogen levels would also be higher due to the larger amount of fat tissue. This idea agrees with a report that women with a nipple aspirate fluid (NAF) phenotype characterized by higher BMI and percentage body fat had higher NAF estrogen levels [ 41 ]. Therefore, the higher PR expression in women with large breasts as compared to women with small breasts may reflect responsiveness to estrogen [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…This may explain the positive association in our study between dietary intake of lactose and milk and being a secretor. Consistent with the ability of the non-lactating breast to synthesize lactose, is our prior observation that α-lactalbumin (protein B of lactose synthase) was present abundantly in nipple aspirate fluids of 1/3 of our non-lactating secretors (25) and also that a strong correlation was found between lactose intake and volume of NAF among secretors in the present study. Therefore, it is tempting to speculate that a higher prevalence of α-lactalbumin might be more easily found in the mammary glands of non-lactating women with a more recent history of pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have demonstrated that modification of the diet is able to alter both the NAF composition and secretory status of some women; for example, high dietary intake of lactose [23] (a milk disaccharide not absorbed intact but metabolized in the intestine to galactose and glucose, and re-synthesized in the mammary gland by lactose synthase) may significantly increase NAF secretion due to its main osmotic property [24], but may also stimulate apocrine breast ductal/lobular cells to increase the pathways of lactose synthase through lactalbumin and galactosyl transferase activities [40,43]. Although the enzymatic involvement of lactose synthase was found only in healthy subjects, several studies have highlighted that lactose intake and its presence in NAF were related to both the active secretory function of apocrine breast cells lining the ducts and to NAF colour [47].…”
Section: Role Of Nutrients In Nipple Aspirate Fluids: Effects On Breamentioning
confidence: 99%
“…For these reasons, a personalized diet on the basis of nutritional status and genotype can be very helpful in preventing and curing human diseases, including cancer. The eventual implementation of these concepts in every-day clinical practice promises to revolutionize the preventive and therapeutic approach to many diseases thereby reducing the need for conventional pharmaceutical therapy fat, body mass index and body fat mass significantly affect both LDL levels and protein profile of NAF, suggesting that gene and protein expression of breast epithelial cells bathing NAF may be strongly influenced by the amounts and types of dietary and body fats [24]. A high fat-diet has been linked to elevated levels of circulating estrogens in women [62] and it was hypothesized to account for considerable variation in breast cancer risk among populations.…”
Section: Role Of Nutrients In Nipple Aspirate Fluids: Effects On Breamentioning
confidence: 99%
See 1 more Smart Citation